Analisis Tingkat Ketidakpuasan Nasabah dalam Penanganan Klaim Produk Asuransi Mitra Mabrur Plus: Studi Kasus PT. AJS Bumiputera KPS Medan - Intan Sakina Br. Nasution; Fauzi Arif Lubis; Muhammad Syahbudi (Universitas Muhammadiyah Enrekang, 2022)
Analysis of the Level of Customer Dissatisfaction in Handling Claims for Mitra Mabrur Plus Insurance Products (Case Study of PT. AJS Bumiputera KPS Medan) Under the guidance of Thesis Advisor I Mr. Dr. Fauzi Arif Lubis, MA. and Supervisor II Mr. Muhammad Syahbudi, MA.This study aims to determine the average insurance customer who is dissatisfied with insurance claims at PT. AJS Bumiputera Kps Medan. This research is a research using descriptive qualitative method. This research was conducted at Mitra Mabrur Plus Insurance Company from PT. AJS Bumiputera Kps Medan. After conducting literature and field reviews and compiling data, the ranking of the level of customer dissatisfaction with client services sequentially starts from the loss survey (53%); Claim documents (53.6%); Premium Checking (55.9%). Meanwhile, the loss report (60.7%) was perceived as satisfactory. Aspects that need improvement as reflected in Quadrant I in the Cartesian diagram include: ease of extracting incident information and ease of obtaining claim forms. In quadrant II in the Cartesian diagram, which consists of: ease of contacting parties. These aspects are reflected in quadrant III which includes: flexibility in terms of premium payment, payment of claims if the premium has not been paid, flexibility in the amount of compensation for events and flexibility in the time frame for preparing claim documents. These aspects are reflected in quadrant IV which includes aspects of the ease of checking running premiums.